2000
DOI: 10.1159/000026635
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Method on Seasonal Distribution of Attempted Suicides in Italy

Abstract: To verify if attempted suicides follow different seasonal distributions according to the method chosen, we studied the Italian monthly distribution of admissions for attempted suicide in the period 1984–1995 according to gender and age, distinguishing between non-violent (ICD 950–952) and violent (ICD 953–958) attempted suicides. The effect of temperature was also taken into account. A clear asymmetry in seasonal distribution of events can be observed in the oldest age groups in both genders, with a peak in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 43 publications
3
46
0
1
Order By: Relevance
“…This finding is consistent with the seasonality of violent suicide attempts in Italy, suggesting a positive relationship between temperatures and violent suicide attempts [28] . Further, no climatic parameter is significant for nonviolent suicide.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is consistent with the seasonality of violent suicide attempts in Italy, suggesting a positive relationship between temperatures and violent suicide attempts [28] . Further, no climatic parameter is significant for nonviolent suicide.…”
Section: Discussionsupporting
confidence: 87%
“…does not clear up the confusion about the effects of weather on suicide. There are other studies with no obvious methodological problems that directly contradict each other (Chew and McCleary 1995;Geltzer et al 2000;Lambert et al 2003;Lester 1999;Linkowski et al 1992;Preti and Miotto 2000;Zung et al 1974). Some of these authors identify positive correlations between weather variables and suicides, some identify negative correlations, and some identify no correlations.…”
Section: Inconsistent Methodsmentioning
confidence: 99%
“…In addition, suicides are quite rare, even among groups of people that are considered to be at a higher risk of committing suicide (Sher 2004). Regardless, many studies have identified significant relationships between suicide and atmospheric variables Lambert et al 2003;Nicholls et al 2006;Partonen et al 2004a;Preti 1997;Preti and Miotto 2000;Salib 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold weather has been shown to alter blood pressure, sympathetic tone, procoagulatory factors, C-reactive protein (CRP) and mood (Woodhouse et al 1994;Kawahara et al 1989). Several investigators have also reported seasonal variations in the incidence of coronary artery disease (CAD) and seasonal affective disorder (SAD), which peak in winter (Moschos et al 2004;Westrin and Lam 2007), and higher suicide rates in warmer months (Preti and Miotto 2000). There is also a predominance of mood disorders in the summer among the Asian population (Ozaki et al 1995;Han et al 2000) as well as in tropical Australia (Morrissey et al 1996).…”
Section: Introductionmentioning
confidence: 99%